Applied satisfiability cryptography, scheduling and coalitional games - Liao, Xiaojuan (Wiley, 2025)
Apply satisfiability to a range of difficult problems The Boolean Satisfiability Problem (SAT) is one of the most famous and widely-studied problems in Boolean logic. Optimization versions of this problem include the Maximum Satisfiability Problem (MaxSAT) and its extensions, such as partial MaxSAT and weighted MaxSAT, which assess whether, and to what extent, a solution satisfies a given set of problems. Numerous applications of SAT and MaxSAT have emerged in fields related to logic and computing technology. Applied Satisfiability: Cryptography, Scheduling, and Coalitional Games outlines some of these applications in three specific fields. It offers a huge range of SAT applications and their possible impacts, allowing readers to tackle previously challenging optimization problems with a new selection of tools. Professionals and researchers in this field will find the scope of their computational solutions to otherwise intractable problems vastly increased. Applied Satisfiability readers will also find: Coding and problem-solving skills applicable to a variety of fields Specific experiments and case studies that demonstrate the effectiveness of satisfiability-aided methods Chapters covering topics including cryptographic key recovery, various forms of scheduling, coalition structure generation, and many more Applied Satisfiability is ideal for researchers, graduate students, and practitioners in these fields looking to bring a new skillset to bear in their studies and careers.
Includes bibliographical references and index
Keywords: Boolean logic; Data encryption (Computer science); Program transformation (Computer programming); Chiffrement (Informatique); Transformation de programme (Informatique)